Cytotoxic Effects of Zerumbone on Ovarian and Cervical Cancer Cell Lines - Mohd Zain, Zetty Nadia (2005)
Globally, ovarian cancer is the fifth most common cancer among women that affects approximately 1 in 75 women in the developed countries. Over 75% of cases were presented at an advanced stage, with disease spread beyond the ovaries. To date, cervical cancer in women remains a major problem with about 400,000 new cases per year and almost 250, 000 reported deaths. However, this disease affects predominantly poor women in underdeveloped countries. It is estimated that 60% of the glcbal market for anticancer and anti-infectious drugs or those under clinical trial are of natural origin. Zerumbone, a sesquiterpene compound isolated from the rhizomes Zingiber zerumbet was shown to suppress TNF-a release and also induces apoptosis in a variety of human colonic adenocarcinoma cell lines. In this current study, the chemotherapeutic potential of zerumbone in cervical cancer (HeLa) and ovarian cancer (Caov-3) cell lines of human origin was evaluated together with cisplatin, a commercially used drug currently used for treating ovarian and cervical cancers. Exposure of both cancer cells to a range of zerumbone concentrations demonstrated growth inhibition in both cancer cells at a dose-dependent manner. The ICso values, determined by the MTT (3-[4,5-dimethylthiazol-2-yl]-2,Sdiphenyltetrazolium bromide) reduction assay were as follows: zerumbone; Caov-3, 24.0 pM (5.2 pg/ml), HeLa, 20.7 pM (4.5 pg/ml) and cisplatin; Caov-3, 3.7 pM (1.1 pglml), HeLa, 5.3 pM (1.6 pg/ml). Laser scanning confocal microscopy following AOIPI staining were used to examine morphological changes of both cancer cells after zerumbone and cisplatin treatment. Apoptotic features that included membrane blebbing and nucleus condensation were evident in both treated cancer cells. Following this, TUNEL (TdT-mediated dUTP Nick-End Labeling) assay was conducted to confirm apoptosis. The studies conducted seems to suggest that zerumbone induce cell death by stimulating apoptosis better than cisplatin, based on significantly higher percentage of apoptotic cells in zerumbone treated cancer cells as compared to cisplatin. In addition, zerumbone and cisplatin arrests cancer cells at G2/M phase as analyzed by flow cytometry. Abnormal synthesis of 1L-6 appears to contribute to the pathogenesis of several kinds of diseases and the constitutive production of IL-6 has been implicated in malignant diseases. Increased levels of IL-6 indicated the aggressiveness of a disease. IL-6 is suggested to provide prognostic value based on its role as a cancer cell growth factor. The effects of zerumbone on IL- 6 levels were studied using a human base ELISA. The results indicated that zerumbone significantly decreased the levels of IL-6 secreted by both cancer cells. However, membrane-bound IL-6 receptor is still intact after zerumbone treatment as demonstrated using immunology fluorescence technique. This study concludes that the compound, zerumbone inhibits both cancer cells growth through the induction of apoptosis, arrests cell cycle at G2/M phase and inhibits the secretion levels of IL-6 in both cancer cells. Therefore, zerumbone is a potential candidate as a useful chemotherapeutic agent in treating both cervical and ovarian cancers in future.